2007
DOI: 10.1634/stemcells.2006-0691
|View full text |Cite
|
Sign up to set email alerts
|

Erasure of Cellular Memory by Fusion with Pluripotent Cells

Abstract: Pluripotent cells have been suggested as a prime source to reprogram somatic cells. We used F9 EC cells as a pluripotent partner to reprogram neurosphere cells (NSCs) because they exhibit a nonneural differentiation potential in the presence of retinoic acid. F9-NSC hybrid cells displayed various features of reprogramming, such as reactivation of pluripotency genes, inactivation of tissue-specific genes, and reactivation of the inactive X chromosome. As the hybrid cells undergo differentiation, the pluripotenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 32 publications
0
29
0
1
Order By: Relevance
“…The fusion hybrid cells carried similar epigenetic characteristics to ES cells (18 -26), which re-exhibited activated histone modifications and a DNA hypomethylation epigenetic state within the Oct4 promoter (24,27). In this research, aberrant epigenetic silencing of p16…”
Section: Hepatocellular Carcinoma (Hcc)mentioning
confidence: 52%
“…The fusion hybrid cells carried similar epigenetic characteristics to ES cells (18 -26), which re-exhibited activated histone modifications and a DNA hypomethylation epigenetic state within the Oct4 promoter (24,27). In this research, aberrant epigenetic silencing of p16…”
Section: Hepatocellular Carcinoma (Hcc)mentioning
confidence: 52%
“…Consequently, one major limiting step in somatic cell reprogramming, namely activation of the endogenous Oct4 locus (35,36), is overcome almost immediately after exogenous factor expression. In Oct4-GFP reporter MEFs, GFP + cells were detected as early as day 3 to 4 after expressing 6F, which is comparable to somatic cell nuclear transfer (37) or cell fusion (38). Therefore, technically, 6F should facilitate further development of nongenetic modifying reprogramming such as using episome and mRNA (39,40).…”
Section: Discussionmentioning
confidence: 92%
“…In a previous study, it was found that the somatic cell genome could be reprogrammed by day 2 postfusion, as evidenced by activation of somatic Oct4-GFP transgene expression, which was detected by visualization of the fluorescence signal, around 44 -48 hours after fusion [17]. According to our unpublished data, reprogrammed Oct4-GFP-positive OG2 hybrids exhibited complete demethylation of the Oct4 PE locus by day 2 postfusion, whereas the hybrids exhibited gradual demethylation of the Oct4 PP locus, which was similar to that of the pluripotent fusion partner F9 EC cells by day 9 postfusion (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…For the derivation of NSCs, brain tissue was collected from 12.5-to 16.5-days post coitum (dpc) OG2/ROSA26 and GOF18 heterozygous female mice according to a previous protocol [17]. Isolated NSCs were grown in DMEM-Ham's F-12 medium (Gibco-BRL) supplemented with 20 ng/ml epidermal growth factor, 20 ng/ml basic fibroblast growth factor, B27 supplement (Gibco-BRL), 8 mM HEPES, 2 mM glutamine, 100 U/ml penicillin, and 100 mg/ml streptomycin.…”
Section: Cell Culturementioning
confidence: 99%
See 1 more Smart Citation